Implementing Best Practices to Redesign Workflow and Optimize Nursing Documentation in the Electronic Health Record - Lindsay, Mary R.; Lytle, Kay (Applied Clinical Informatics, 2022)
Background Documentation burden associated with electronic health records (EHR) is well documented in the literature. Usability and functionality of the EHR are considered fragmented and disorganized making it difficult to synthesize clinical information. Few best practices are reported in the literature to support streamlining the configuration of documentation fields to align clinical workflow with EHR data entry elements.Objective The primary objective was to improve performance, reduce duplication, and remove nonvalue-added tasks by redesigning the patient assessment template in the EHR using best practice approaches.Methods A quality improvement approach and pre-/postdesign was used to implement and evaluate best approaches to redesign standardized flowsheet documentation workflow. We implemented standards for usability modifications targeting efficiency, reducing redundancy, and improving workflow navigation. The assessment type row was removed; a reassessment section was added to the first three flowsheet rows and documentation practices were revised to document changes from the initial assessment by selecting the corresponding body system from the dropdown menu. Vendor-supplied timestamp data were used to evaluate documentation times. Video motion-time recording was used to capture click and scroll burden, defined as steps in documentation, and was analyzed using the Keystrok Level Model.Results This study's results included an 18.5% decreased time in the EHR; decrease of 7 to 12% of total time in flowsheets; time savings of 1.5 to 6.5 minutes per reassessment per patient; and a decrease of 88 to 97% in number of steps to perform reassessment documentation.Conclusion Workflow redesign to improve the usability and functionality decreased documentation time, redundancy, and click burden resulting in improved productivity. The time savings correlate to several hours per 12-hour shift which could be reallocated to value-added patient care activities. Revising documentation practices in alignment with redesign benefits staff by decreasing workload, improving quality, and satisfaction.
Keywords: flowsheets; patient reassessment; documentation burden; electronic health records; workflow evaluation; redesign; nursing